Adaptações na estrutura em Y no manejo da Uva Niágara Rosada voltadas para um melhor custo-benefício - Oliveira, Gabriel Fortes de (Universidade Federal de São Carlos, 2022)
Y-Grape production is a well-known driving system used in most table grape producing regions in the country. With great advantages, such as better structure of bunches and more adequate posture of the farmer during all production processes, compared to the conventional system in backrest, its popularization was very fast and well accepted by most producers. However, some winegrowers did not adhere to this new way of driving because it presented a high cost of implantation, thus hindering its implementation in the field. In the present work carried out at sítio Santa Bárbara located in the municipality of Jundiaí, in the state of São Paulo, adaptations were made in the dimensions of the "Y" structure and use of the moors of the old backrest, as well as its wire, reducing the cost of implementing this new structure for the management of reusable materials of the Niagara grape. By modifying the dimensions and reusing the materials of the old backrest of the property for the manufacture of the modified Y-structure, it was possible to reduce costs by almost 60% in the implanted area, without changing the quality of production and the other benefits that conventional Y offers. Thus it was possible to save a large amount that would be spent on structure and that can now be allocated for other investments.
Y-structure adaptations in the management of Niagara Rosada grape aimed at a better cost-benefit
Keywords: Vitis labrusca; Reutilização de materiais; Uva de mesa; Bem-estar do produtor; Produção familiar; Economia; Reuse of materials; Table grape; Well-being of the producer; Family production; Economy; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA